PENGEMBANGAN MEDIA PEMBELAJARAN KARTU KUARTET BERBASIS APLIKASI CANVA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SD - Manalu, Eka Widawati; Gandamana, Apiek; Simanjuntak, Eva Betty; Halimatussakdiah, Dr.; Afriadi, Putra (Jurnal Merah Putih Sekolah Dasar, 2024)
This research is motivated by the problem of limited learning media, which causes difficulties for students in understanding the material during the learning process. This study aims to determine the feasibility, practicality, and effectiveness of Canva application-based quartet card learning media for the Pancasila Education subject in Grade IV at SD Negeri 060872, Medan Perjuangan District. This type of research is developmental research (Research and Development) with the 4-D model, consisting of four stages: define, design, development, and disseminate. The subjects of this study were 21 students from Grade IV at SDN 060872, Medan Perjuangan District. Data collection techniques used in the research were interviews, questionnaires, tests, and documentation. This research and development resulted in a product of Canva application-based quartet cards for the Pancasila Education subject in Grade IV at SD Negeri 060872, Medan Perjuangan District. The data analysis techniques used in this study were qualitative and quantitative. The research results show that 1). The feasibility test was categorized as "feasible" with the material expert validator scoring 84% and the learning design expert validator scoring 95%, categorized as "highly feasible". 2). The practicality test by the Grade IV teacher scored 92%, categorized as "highly practical". The effectiveness test showed an average pre-test score of 57.1, categorized as "incomplete", and an average post-test score of 83.3, categorized as "complete". The test results indicate an increase in scores, showing that the quartet cards are effective to be implemented in schools with the qualification of being highly practical. Thus, the Canva application-based quartet cards for the Pancasila Education subject in Grade IV at SD Negeri 060872, Medan Perjuangan District, are declared feasible, practical, and effective as teaching materials that create active and effective learning.